Transforming the Dutch welfare state : Social risks and corporatist reform - Yerkes, Mara (Book collections on Project MUSE., 2011)
This comprehensive study demonstrates the dramatic changes that have taken place in the protection of old and new social risks, exploring the mechanisms behind these changes in the context of corporatist welfare state institutions.